(untitled) (Konferensiyalar | Conferences, 2024)
In this article, we delve into the sociolinguistic impact of language on its speakers. Amongst language, humanity build and express their cultural self-conception, reflecting their connection with particular social groups or communities. In addition, it explores how linguistic variance and dialects show how language can bring people together as well as drive them apart. Furthermore, it examines the ways in which language shapes interpersonal partnerships, maintains stereotypes, and conveys social status. The present study aims to increase knowledge of the complex partnership among language and society by providing light on the different ways that language affects its speakers.